1998
DOI: 10.1176/ajp.155.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment Attrition in a Comparative Treatment Outcome Study on Panic Disorder

Abstract: Results from comparative treatment outcome studies are limited not only to people who meet the study criteria but also to those who are willing to begin a medication treatment and discontinue their current medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(43 citation statements)
references
References 13 publications
2
41
0
Order By: Relevance
“…Recently, it has been reported that patients with PA refuse medication at much higher rates than CT [10]. In the present study, there were no patients who refused randomization because they were unwilling to accept CT.…”
Section: Discussionmentioning
confidence: 52%
“…Recently, it has been reported that patients with PA refuse medication at much higher rates than CT [10]. In the present study, there were no patients who refused randomization because they were unwilling to accept CT.…”
Section: Discussionmentioning
confidence: 52%
“…This pattern is suggestive of a self-selection bias that may limit interpretation of study findings to those individuals in clinical practice willing to accept novel medications, and exemplifies the importance of including such information in PTSD outcome research. This potential constraint on external validity has been similarly noted in research on other Axis I disorders (Hofmann et al, 1998).…”
Section: Enrollment and Baseline Psychopathology In A Recently Complementioning
confidence: 74%
“…The impact on study validity of pretreatment attrition, or the refusal to participate by potentially eligible participants, has yet to be studied in PTSD outcome research. Efficacy research on other Axis I disorders has revealed self-selection patterns in study enrollment (e.g., differential refusal of medication vs. psychotherapy treatment conditions) that may limit generalization of study findings (Hofmann et al, 1998). Implications for the external validity of PTSD outcome research comparing pharmacotherapy to psychotherapy are addressed below in examination of pretreatment attrition data from the first randomized clinical trial (RCT) of this kind.…”
Section: Attritionmentioning
confidence: 99%
“…If a research study enrollee is assigned to a control condition that appears to be no better than previously received services, the enrollee may enter into the assigned program halfheartedly or refuse services altogether (1,12). Likewise, if study enrollees have to relinquish a current service to participate in an experimental program, they may delay contacting the assigned program or withdraw from project participation (13,14).The present study investigates the impact of preference in experimental condition assignment on study applicants' motivation to enroll in a mental health services research project, engage in assigned services, and pursue the project's targeted outcomes. …”
mentioning
confidence: 99%